2017
DOI: 10.1177/1715163517690744
|View full text |Cite
|
Sign up to set email alerts
|

Risk of falls associated with antiepileptic drug use in ambulatory elderly populations

Abstract: Background: Falls are a major cause of morbidity and mortality in older adults. About a third of those aged 65 years or older fall at least once each year, which can result in hospitalizations, hip fractures and nursing home admissions that incur high costs to individuals, families and society. the objective of this clinical review was to assess the risk of falls in ambulatory older adults who take antiepileptic drugs, medications that can increase fall risk and decrease bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The prevalence of suspected medication-related falls is about 41% [ 555 ] to 49% [ 556 ]. Increased risk of falls was documented in users of anxiolytics/hypnotics, opioids, sedatives, antihypertensives (especially alpha-blockers), antidepressants, antiparkinsonian medications, antiepileptics and antiarrhythmics [ 557 , 558 , 559 , 560 , 561 , 562 , 563 , 564 , 565 , 566 , 567 , 568 , 569 , 570 , 571 , 572 , 573 , 574 , 575 , 576 , 577 , 578 , 579 , 580 , 581 , 582 , 583 ]; polypharmacy is strongly associated with injurious falls and fractures [ 574 , 582 , 584 , 585 , 586 , 587 , 588 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…The prevalence of suspected medication-related falls is about 41% [ 555 ] to 49% [ 556 ]. Increased risk of falls was documented in users of anxiolytics/hypnotics, opioids, sedatives, antihypertensives (especially alpha-blockers), antidepressants, antiparkinsonian medications, antiepileptics and antiarrhythmics [ 557 , 558 , 559 , 560 , 561 , 562 , 563 , 564 , 565 , 566 , 567 , 568 , 569 , 570 , 571 , 572 , 573 , 574 , 575 , 576 , 577 , 578 , 579 , 580 , 581 , 582 , 583 ]; polypharmacy is strongly associated with injurious falls and fractures [ 574 , 582 , 584 , 585 , 586 , 587 , 588 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Furthermore, pooled data of movement disorders and falls showed significantly more events in participants treated with anticonvulsants compared with placebo [61,63]. Two other reviews regarding the use of antiepileptic drugs in older patients also showed an association between anticonvulsant treatment and falls in older patients [93,94].…”
Section: Anticonvulsantsmentioning
confidence: 97%
“…classes with an increased risk of falls. [11][12][13][14][15][16][17][18][19][20] Examples of identified drug classes with an increased fall risk are antiarrhythmic drugs, antidepressants, psychotropic drugs and diuretics. 1 8-11 Different strategies and tools to prevent fall incidents are developed.…”
Section: Open Accessmentioning
confidence: 99%